2015
DOI: 10.1016/j.sjbs.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Histological, molecular and biochemical detection of renal injury after Echis pyramidum snake envenomation in rats

Abstract: Nephrotoxicity is a common sign of snake envenomation. The present work aimed to clarify the effect of intraperitoneal injection of 1/8 LD50 and 1/4 LD50 doses of Echis pyramidum snake venom on the renal tissue of rats after 2, 4 and 6 h from envenomation. Histopathological examination showed intense dose and time dependent abnormalities, including swelling glomerulus and tubular necrosis and damage as well as signs of intertubular medullary hemorrhage at early stages of envenomation. However, at late stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…In this study the pathological effect of each regional venom sample according to the time of venom administration was evaluated and the pathological data witnessed a toxic effect exerted within 1 hour after IM injection regardless to their originated location. Similar to previous records on relationship between effects of envenomation with the time of envenomation [ 52 ] current study also found severity of the venom increasing parallel to the time.…”
Section: Discussionsupporting
confidence: 90%
“…In this study the pathological effect of each regional venom sample according to the time of venom administration was evaluated and the pathological data witnessed a toxic effect exerted within 1 hour after IM injection regardless to their originated location. Similar to previous records on relationship between effects of envenomation with the time of envenomation [ 52 ] current study also found severity of the venom increasing parallel to the time.…”
Section: Discussionsupporting
confidence: 90%
“…Although there are numerous reasons for renal cell death, the pathophysiology is the same and is typically associated with an impairment in the microcirculation. This mismatch between the delivery of oxygen and nutrients to the nephrons and increased energy demands (increased oxidative stress, loss of ATP) leads to inflammation, vascular and tubular injury, and alteration in kidney biochemical parameters and oxidative stress markers 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Nephropathy induced by snake venom was mentioned by Vikrant et al [ 1 ]. Histo-pathological examination showed intense dose and time dependent abnormalities, including swelling glomerulus and tubular necrosis and damage as well as signs of intertubular medullary hemorrhage at early stages of envenomation in kidney sections [ 2 ]· Viper envenomation is associated with degeneration and necrosis. Focal glomerulonephritis is common.…”
Section: Introductionmentioning
confidence: 99%